Strategies for Introducing Clean and Healthy Living Behaviors for Early Childhood in the New Normal Period - Mai Siska; Dadan Suryana (Bisma The Journal of Counseling, 2022)
The introduction of clean and healthy living is very important for early childhood , especially during the new normal period of Covid-19, children still have to maintain cleanliness and health from various diseases or viruses that exist in the surrounding environment. The purpose of this paper is to determine the strategy of introducing Clean and Healthy Living Behavior (PHBS ) in order to obtain an overview and analyze the implementation of clean living behavior in early childhood. The method used in this article is a literature study, for initial preparation in preparing the research framework. Based on the results of previous studies, it was found that the introduction of a clean and healthy life can be done by getting used to a healthy and clean lifestyle by reminding children to eat nutritious foods such as vegetables and fruit, exercising regularly and getting enough rest and doing sunbathing every morning around 10-15 minutes, wash hands with soap, and maintain personal hygiene